PERCEPTION DIFFERENCES OF LIBRARY SERVICE QUALITY AT STUDENTS OF COMPUTER SCIENCE FACULTY AND STUDENT OF ECONOMICS & BUSINESS FACULTY DIAN NUSWANTORO UNIVERSITY SEMARANG - Silya Dewi; Kartika Febrian Kristiana (Faculty of Psychology, Diponegoro University, 2013)
Currently, the use of the college library by students felt less. The development of a library can be seen from the service, because the success of the service is the ultimate goal to be achieved by the library. Whether or not the service quality is influenced by the perception of each user. This study aimed to determine whether or not differences in perceptions of library service quality at students of computer science faculty and economics & business faculty Dian Nuswantoro University Semarang.Population was students in the years 2010-2012 of computer science faculty and economics & business faculty who had ever visited the library of the Dian Nuswantoro University. Subjects was 60 people acquired through accidental sampling technique. Retrieval of data using a scale of perceptions of library service quality consisting of 33 aitem (α = 0.919).Processing data using Independent Samples t-Test, the value generated t = -2.130 and significance 0,041 (p <0,05). It means there are differences in the perception of library service quality at students of computer science faculty and economics & business faculty, so the hypothesis is accepted. Perceptions of library service quality at economics & business students is more positive than computer science students which is 97,40> 91,50.